An excipient-free "sugar-coated bullet" for the targeted treatment of orthotopic hepatocellular carcinoma. Issue 36 (1st September 2022) - Liu, Feiyang; Liu, Lingyan; Liu, Dongya; Wei, Peng; Feng, Wei; Yi, Tao
Abstract : An excipient-free nanoformulation is prepared by a reactive oxygen species-responsive prodrug. These sugar-coated bullets selectively target tumor cells, resulting in high in vivo therapeutic efficacy in an orthotopic HCC mouse model. Abstract : Several components of traditional nanoformulations that result in structural heterogeneity, poor reproducibility, excipient-trigged biotoxicity, and low retention of antitumor drugs in neoplastic foci are important barriers limiting clinical translation. We report an excipient-free nanoformulation prepared by a reactive oxygen species (ROS)-responsive amphiphilic prodrug (Gal-MB-DOX ) for the targeted treatment of orthotopic hepatocellular carcinoma (HCC). Gal-MB-DOX can form monocomponent nanoparticles with a galactose-rich surface similar to a "sugar-coated bullet" through self-assembly in aqueous solution. This nanoformulation can be decomposed quickly by ROS and release free hydrophobic drugs that further precipitate into larger particles, potentially promoting the retention of drugs in tumor cells. These sugar-coated bullets selectively target tumor cells through passive and active targeting, resulting in high in vivo therapeutic efficacy in an orthotopic HCC mouse model. This monocomponent nanomedicine system provides a simple but effective strategy for the treatment of tumors.